THE INFLUENCE OF THE REPAIR SURFACE ON THE STRENGTH OF CONCRETE CONTACT JOINTS - Mazurak , А.; Horal , В.; Mazurak , Т.; Tsap , О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Buildings and structures after long-term use of concrete and reinforced concrete need repair, restoration and strengthening. This is due to many factors, material defects, damage during operation, design errors, etc. The strength of the bond between old and new concrete or shotcrete during repair joints varies, and it depends on several factors, namely the age of the old and new concrete; nature of surface preparation; method of entry and hardening conditions. The experience of repairing and strengthening reinforced concrete structures demonstrates that shotcrete technology is effective for restoring or repairing cement and concrete surfaces. This technology allows for the mechanization of all processes, from surface preparation to the application of dense shotcrete layers, ensuring strong adhesion between the layers. The study examines factors that influence the performance of the contact seam, the repair surface, and the layer matrix. To analyze their interactions, 72 concrete samples were prepared under laboratory conditions, featuring four surface treatments: smooth (a flat surface cleaned with a wire brush), smoothly milled (milling on a flat surface), rough (notches applied to the concrete surface), and rough milled (the surface notched and then milled and cleaned with a wire brush). In the work, the authors experimentally evaluate the bond strength of concrete and shotcrete, having prepared the surface and installed metal clips on it. The inner space of the cage is filled with concrete or a layer of shotcrete is applied. After proper aging in normal conditions and in 28–32 days, the samples are subjected to research, tearing off the metal clip from the concrete surface. The experimental results lead to specific conclusions, particularly that milling concrete samples, whether rough or smooth, does not enhance adhesion with shotcrete.